MicroRNA Content of Ewing Sarcoma Derived Extracellular Vesicles Leads to Biomarker Potential and Identification of a Previously Undocumented EWS-FLI1 Translocation. Issue 17 (October 2022) - Crow, Jennifer; Samuel, Glenson; Farrow, Emily; Gibson, Margaret; Johnston, Jefferey; Guest, Erin; Miller, Neil; Pei, Dong; Koestler, Devin; Pathak, Harsh; Liang, Xiaobo; Mangels, Cooper; et al.
Objective: Ewing Sarcoma Family of Tumors (ESFT) are a highly aggressive pediatric bone and soft tissue malignancy with poor outcomes in the refractory and recurrent setting. Over 90% of Ewing Sarcoma (ES) tumors are driven by the pathognomonic EWS-ETS chimeric transcripts and their corresponding oncoproteins. It has been suggested that the EWS-ETS oncogenic action can mediate microRNA (miRNA) processing. Importantly, small extracellular vesicles (sEVs), including those frequently referred to as exosomes have been shown to be highly enriched with tumor-derived small RNAs such as miRNAs. We hypothesized that ESFT-specific sEVs are enriched with certain miRNAs which could be utilized toward an exo-miRNA biomarker signature specific to this disease.Methods: We performed miRNAseq to compare both the exo-derived and cell-derived miRNA content from 8 ESFT, 2 osteosarcoma, 2 non-cancerous cell lines, and pediatric plasma samples.Results: We found that sEVs derived from ESFT cells contained nearly 2-fold more number of unique individual miRNAs as compared to non-ESFT samples. Quantitative analysis of the differential enrichment of sEV miRNAs resulted in the identification of 62 sEV-miRNAs (exo-miRNAs) with significant ( P < .05) enrichment variation between ESFT and non-ESFT sEV samples. To determine if we could utilize this miRNA signature to diagnose ESFT patients via a liquid biopsy, we analyzed the RNA content of total circulating sEVs isolated from 500 µL plasma from 5 pediatric ESFT patients, 2 pediatric osteosarcoma patients, 2 pediatric rhabdomyosarcoma patients, and 4 non-cancer pediatric controls. Pearson's clustering of 60 of the 62 candidate exo-miRNAs correctly identified 80% (4 of 5) of pathology confirmed ESFT patients. Importantly, RNAseq analysis of tumor tissue from the 1 outlier, revealed a previously uncharacterized EWS-FLI1 translocation.Conclusions: Taken together, these findings support the development and validation of an exo-miRNA-based liquid biopsy to aid in the diagnosis and monitoring of ESFT.